SOME REEFLECTIONS ON THE MINARETS OF UZBEKISTAN (ANCIENT AND MEDIEVAL PERIOD) (Scientific journal of the Fergana State University, 2023)
The article discusses the history of the construction of minarets, their functions, the spread of Islamic architecture in the construction of minarets, the history of the construction of minarets, the architectural style, the functions of minarets in Central Asia, in particular on the territory of Uzbekistan. The article analyzes the dynamic changes in the design of minarets in chronological order.